O aspecto afetivo da conduta : um estudo sobre a motivação para o tratamento da dependência química - Schimith, Polyana Barbosa (2018)
The present thesis aims at investigating the affective aspects involved both in the motivation to spontaneously seek treatment for chemical addiction and the motivation to sustain said treatment. Empirical, qualitative and exploratory, research was carried out in five case studies. For collection of data, we used a series of four semi structured interviews with each participant. Five men who were interned patients in a supporting clinic for recovery of chemical addiction in the metropolitan region of Vitória participated in the research. For data approach and analysis we used the Analysis of Contents. For the investigation and participation of affectiveness in the change of conduct, and as result thereof, in the decision of cutting off the bonds with the drug and seek treatment, we adopted the approach regarding motivation, as presented by Jean Piaget (1954/2014a), which presents affectiveness as a trigger of actions. Main results show that at the moment of making the decision of seeking treatment, participants were under intense suffering. Throughout treatment, the feeling of guilt lingered and reinforced the action of carrying on with it. Breaking up the relationship with the drug, besides guilt, triggered other feelings such as craving, sadness, shame and fear. Such feelings might both motivate the continuing or the interruption of drug consumption. Based on said data, with a psychoanalytic reference (Lacan, 1975/2016), we have come to the understanding that chemical addiction is about a relationship of joy by the subject and the object of the drug, in which the subject often gets reduced to the very drug itself. Thus, in the psychoanalytic perspective, we examined the function of the superego and its imperative of joy in the addiction; as well as the importance of the feeling of guilt in the motivation towards treatment. Main results show that in the clinical praxis it is rather complicated to strengthen the superego through guilt; in regards of breaking up the relationship with the drug, which has always occurred in a unpredictable manner